The controlled release profile of risedronate emulgel to inhibit relapse movement in orthodontic treatment - Utari, Tita Ratya; Kurniawan, Muhammad Fariez; Andewa, Shylvia Muchsin (Padjadjaran Journal of Dentistry, 2022)
Introduction: Relapse is one of the undesirable effects of orthodontic treatment. Prevention of relapse has been carried out with the use of retainer devices. Several studies also have been carried out to prevent relapse with pharmacological agents such as bisphosphonates. One of the strongest bisphosphonates is risedronate. Systemic use of bisphosphonates can cause bisphosphonate-related necrosis of the jaw (BRONJ). Systemic effects can be minimised by topical preparations locally, where the virgin coconut oil (VCO) emulgel is one of the topical preparations which controls the release of drugs. This study aims to analyse the release profile of risedronate emulgel as a material to inhibit relapse movement. Methods: This research was conducted in an experimental laboratory. Group 1 was emulgel without bisphosphonate risedronate with virgin coconut oil (VCO), Group 2 was VCO emulgel with bisphosphonates risedronate, and Group 3 was a pure bisphosphonate risedronate solution. Each group weighing 100 mg was placed in 10 ml PBS, and the release test was conducted with UV/VIS Spectrophotometer wavelength λ 262 nm at intervals of 1, 2, 4, 8, 24, 48, and 96 hours with three replications at each group. Results: Grup 2 yielded a controlled drug release of risedronate until 96 hours, while a pure solution of risedronate resulted in an uncontrolled drug release of risedronate, which was released entirely in 4 hours. Conclusion: Risedronate emulgel with VCO had a controlled drug release compared to pure bisphosphonate solution to potentially be applied topically to inhibit relapse movement.